Improving the retention of underrepresented minority faculty in academic medicine. - Daley, Sandra (National Medical Association, 2006)
BACKGROUND: Although several studies have outlined the need for and benefits of diversity in academia, the number of underrepresented minority (URM) faculty in academic health centers remains low, and minority faculty are primarily concentrated at the rank of assistant professor. In order to increase the diversity of the faculty of the University of California, San Diego (UCSD) School of Medicine, the UCSD National Center for Leadership in Academic Medicine, in collaboration with the UCSD Hispanic Center of Excellence, implemented a junior faculty development program designed in part to overcome the differential disadvantage of minority faculty and to increase the academic success rate of all faculty. METHODS: Junior faculty received counseling in career and research objectives; assistance with academic file preparation, introduction to the institutional culture; workshops on pedagogy and grant writing; and instrumental, proactive mentoring by senior faculty. RESULTS: After implementation of the program, the retention rate of URM junior faculty in the school of medicine increased from 58% to 80% and retention in academic medicine increased from 75% to 90%. CONCLUSION: A junior faculty development program that integrates professional skill development and focused academic career advising with instrumental mentoring is associated with an increase in the retention of URM faculty in a school of medicine.